2020
DOI: 10.3390/met10030332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Pass Caliber Rolling on Dilute Extruded Mg-Bi-Ca Alloy

Abstract: A Mg-1.32Bi-0.72Ca (BX11) alloy having bimodal grain structure was successfully prepared by a novel processing route of combining extrusion and three-pass caliber rolling. The first extruded and then caliber-rolled (E-CRed) alloy demonstrates a necklace-like grain structure with ultrafine grains formed around the microscale deformed grains, which is remarkably different from the uniform microstructure of the as-extruded alloy. In addition, the E-CRed BX11 alloy exhibits strong basal texture which is mainly ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…As shown in Figure 2a,c, a small amount of micro-scale white second particles can be detected distributed along the ED in the matrix, which were further characterized as Mg-Bi, Mg-Bi-Ca, and Mg-Ca intermetallics by the EDS results in Figure 2d. The particles containing the same elements were identified as Mg 3 Bi 2 , Mg 2 Bi 2 Ca, and Mg 2 Ca phases, respectively, in previously reported Mg-Bi-Ca alloys [17][18][19].…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…As shown in Figure 2a,c, a small amount of micro-scale white second particles can be detected distributed along the ED in the matrix, which were further characterized as Mg-Bi, Mg-Bi-Ca, and Mg-Ca intermetallics by the EDS results in Figure 2d. The particles containing the same elements were identified as Mg 3 Bi 2 , Mg 2 Bi 2 Ca, and Mg 2 Ca phases, respectively, in previously reported Mg-Bi-Ca alloys [17][18][19].…”
Section: Resultsmentioning
confidence: 65%
“…It is reported that, when 3-8% Bi is added to pure Mg, the TYS of the extruded samples can be increased by 88 MPa to 129 MPa, mainly because of the grain refinement and precipitation strengthening by fine Mg 3 Bi 2 2 of 7 phases [11,12]. Additionally, Al, Zn, Sn, Ca, and Mn have been introduced into Mg-Bibased alloys to improve their mechanical properties [13][14][15][16][17][18][19][20]. For example, by alloying an Mg-Bi-based alloy with Al and Zn, an extruded Mg-8Bi-1Al-1Zn (BAZ811) alloy exhibiting a TYS of 291 MPa and an elongation of 14.6% was fabricated in our former research [13].…”
Section: Introductionmentioning
confidence: 99%
“…The UTS of the BAZ631 sample is much higher than that of B6 [7], and even higher than that of the more Bi concentrated BAZ811 sample [16]. The RE-free BAZ631 alloy by simple one-step extrusion in this study shows much higher UTS than that of Mg-Bi-Ca alloy processed by combining extrusion and caliber rolling [14], which ranks first among all the previously reported Mg-Bi-based alloys until now. It is widely accepted that the microstructure characteristics, such as AGS, second phase particles, and solute atoms in the Mg alloys, significantly affect their mechanical properties.…”
Section: Resultsmentioning
confidence: 58%
“…H. Somekawa et al [9] reported that Mg-3Bi alloy can be extruded at the temperature less than 210 • C and demonstrates an EL of 170%. Additionally, Ca [10][11][12][13][14], Si [10], Mn [15], Al [16], Zn [16], and Sn [17] have been used as alloying elements to improve the mechanical properties of Mg-Bi based alloys. For example, biomedical Mg-5Bi-1Ca/Si alloys having an EL of over 40% were successfully fabricated by the rapid solidification and extrusion process [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation